Investigation on Wall Cracking by Using Visual Inspection and Determine The Suitable Methods for Maintenance Action - Bong, Zhang Min; Mohammad Ashraf Abdul Rahman (Progress in Engineering Application and Technology, 2022)
Malaysia is one of the developing countries with significant growth in many fields, including the construction industry. Cracking walls in existing constructions is one of the components that need to be a concern. The problems happen due to environmental impact, poor construction, or, malfunctioning of the system, and so on. Therefore, the study is carried out to investigate what are the problems that lead to wall cracked and how the wall cracked happen. Then, the solution to solve the cracking wall is based on the wall needed to repair, maintenance, or rehabilitation. Moreover, the study will be conducted at Sekolah Jenis Kebangsaan (SJKC) Chung Hua Kranji. The method to carry out the study is visualized and Building Condition Assessment (BCA). The data or information are collected through inspection on-site and recorded by taking photos. This method is used to determine and classify the types and the causes of the wall. The results are analyzed by interpretation. According to the study, the causes of cracking walls may be in many reasons such as lack of supervision, temperature surrounding, poor construction, failure, etc. Of course, there are many types of repair methods to propose, and the proposed method depends on the severity of the cracking. Moreover, the methods to overcome the cracking wall are based on the Building Condition Assessment. After the research, most of the SJK Chung Hua Kranji’s cracking wall rated in very good and good rating. So, the solution to overcome the cracking wall is maintenance based on the condition.